1997
DOI: 10.1007/s11626-997-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of SV40 immortalized rat submandibular acinar cell lines

Abstract: Rat submandibular salivary gland acinar cells were transfected by CaPO4 precipitation using a plasmid containing a replication-defective simian virus (SV40) genome. Out of 27 clonal cell lines, two were shown to have moderate to high levels of cytodifferentiation and salivary gland acinar cell function. Functional studies with the two cell lines indicated that the beta-adrenergic agonist, isoproterenol, vasoactive intestinal peptide, and prostaglandin E1 were effective activators of intracellular cyclic AMP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 18 publications
4
83
0
Order By: Relevance
“…Because there is no appropriate cell line derived from either human or rabbit SMGs for further study on tight-junction structure and function, we chose the rat SMG-C6 cells to characterize the effect of TRPV1 on SMG epithelia. This cell line, originally established by Quissel et al, was reported to maintain a normal acinar function and have similar characteristics, including tight junction structure, as determined by electron microscopy (Quissell et al, 1997). In the present study, we confirmed the expression of TRPV1 and occludin and characterized their distribution.…”
Section: Discussionsupporting
confidence: 83%
“…Because there is no appropriate cell line derived from either human or rabbit SMGs for further study on tight-junction structure and function, we chose the rat SMG-C6 cells to characterize the effect of TRPV1 on SMG epithelia. This cell line, originally established by Quissel et al, was reported to maintain a normal acinar function and have similar characteristics, including tight junction structure, as determined by electron microscopy (Quissell et al, 1997). In the present study, we confirmed the expression of TRPV1 and occludin and characterized their distribution.…”
Section: Discussionsupporting
confidence: 83%
“…), and VOL. 26,2006 SUPPRESSION OF SALIVARY ACINAR CELL APOPTOSIS BY Akt 8841 primary parotid or submandibular acinar cells were prepared under sterile conditions similar to previously published protocols (50,51,72 (3,51). Activation of caspase 3 was quantitated with the BioMol QuantiZyme Colorimetric assay kit (Plymouth Meeting, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized with sodium pentobarbital (60 mg/kg) and primary parotid acinar cells were prepared under sterile conditions similar to previously published protocols used in the preparation of primary acinar cells from rat salivary glands. 48 A 1% vol/vol cell suspension was seeded onto collagen-coated dishes (Falcon/Becton Dickenson) in media similar to that used for the established cell lines with the exception of the FBS content elevated from 2.5 to 10%. Cells reached approximately 80% confluency after 5 days in culture and were utilized immediately in experiments at that time without passage.…”
Section: Cells and Cell Culturementioning
confidence: 99%